A study in the commedia dell'arte, 1560-1620 - Katritzky, M; Katrizky, M. A. (1995)
The research field addressed by this thesis is the commedia dell'arte and its iconography in the period preceding Callot's Balli di Sfessania engravings of c. 1621. Its main aim is to provide a broad overview of the surviving early pictures in order to contribute towards a more detailed understanding of the history of the commedia deH'arte in the opening decades of its existence, 1560-1620, by using late renaissance pictures as a documentary source. My research method has three main steps. These are firstly, the identification of relevant pictures, on the basis of a detailed understanding of the early history of the commedia dell'arte, and taking a deliberately inclusive approach; secondly, the classification of such pictures according to art-historical methods, in order to associate them with specific named artists so that they can be placed in the context of an oeuvre and place of production; thirdly, interpretation of their theatrical content. Integral to the thesis are the 340 plates. Many feature pictures which were anonymous or implausibly attributed, and unknown to theatre historians, before they appeared here or in my publications. My inclusive approach has contributed towards the marked rehabilitation of carnival pictures which is evident in the most recent scholarship in this area. My new discoveries, and attributions and re-attributions of some of the 340 plates, summarized in the plate list, have enabled me to identify significant bodies of commedia-related pictures by a number of named late renaissance artists not previously associated with theatre iconography, and provide a broad overview of the early stock types, their costumes and settings; contributions which are stimulating further research in this area. Section I summarises the rise and spread of professional acting in sixteenth century Italy, some forerunners of the commedia dell'arte, and its early stock types. It also presents new documentary material, discovered in the course of my archival researches, which is relevant to the earliest commedia performance for which a comprehensive description survives, staged in Munich in 1568. Section II presents art-historical analyses of three groups of prints in Stockholm, and six paintings which are the subject of an article published in 1943. It also presents an overview of a large group of Flemish pictures whose relation to two Italian prints demonstrates the progressive stereotyping of commedia-related motifs which was already occurring around 1600. Section III offers theatrical interpretations of the pictures, concentrating on scenery, set and stages; actresses; a selection of stock characters, including Harlequin, Zanni and Pantalone, and also some less wellknown figures such as tedescos and matachins; and multiple and serial images. The renaissance Italian comedians' multiple roots in amateur humanist comedy, professional entertainment and popular carnival ritual gave them their early creativity and wide appeal, and left their mark on the iconography which, by the seventeenth century, like the commedia dell'arte itself, was, for the most part, settling into a predictable routine based on precedents and conventions.